Kemampuan Menulis Teks Eksposisi siswa Fase X SMA Negeri 8 Padang Menggunakan Model Discovery Learning - Sindi Irawati; Najmi Hayati; Susanti Marisya (JURNAL ARMADA PENDIDIKAN, 2024)
This study was motivated by students’ still low ability in writing exposition texts, particularly in developing a thesis statement, constructing arguments supported by evidence, and presenting a logical reiteration. The study aimed to describe the ability to write exposition texts through the implementation of the Discovery Learning model among Phase X students of SMA Negeri 8 Padang. This research employed a quantitative approach with a descriptive method. The subjects were 36 students of Phase X.E4 selected through purposive sampling from a population of 350 Phase X students. The data were collected through a performance test in writing exposition texts and documentation. The data were analyzed by selecting students’ written work, scoring it based on an assessment rubric covering the opening (thesis), body (arguments and evidence), and closing (reiteration), converting the scores into grades, calculating the mean scores, and then describing the results according to the assessment classification. The findings showed that the students’ ability in writing exposition texts was classified as very good, with an overall mean score of 86.72. In detail, the thesis aspect obtained a mean score of 84.26, which was categorized as good; the arguments and evidence aspect obtained 88.89, which was categorized as very good; and the reiteration aspect obtained 88.03, which was also categorized as very good. The implication of this study is that the Discovery Learning model can be used as an effective alternative in improving students’ ability to write exposition texts in a more logical, systematic, and well-directed manner.